2015
DOI: 10.1128/aem.00609-15
|View full text |Cite
|
Sign up to set email alerts
|

DNA Microarray-Based Identification of Genes Regulated by NtrC in Bradyrhizobium japonicum

Abstract: eThe Bradyrhizobium japonicum NtrBC two-component system is a critical regulator of cellular nitrogen metabolism, including the acquisition and catabolism of nitrogenous compounds. To better define the roles of this system, genome-wide transcriptional profiling was performed to identify the NtrC regulon during the response to nitrogen limitation. Upon cells perceiving low intracellular nitrogen, they stimulate the phosphorylation of NtrC, which induces genes responsible for alteration of the core glutamine syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
2
7
1
4
Order By: Relevance
“…The second core cytoplasmic enzyme component of the NO 3 − assimilation pathway is NirA, which is required for growth on either NO 3 − or NO 2 − as sole N-source. Consistent with our findings, it has recently been demonstrated that NirA (encoded by bll4571) is required for utilization of NO 3 − or NO 2 − as sole N-source in B. japonicum [ 46 ]. NO 3 − -dependent induction of nasC (as part of the narK operon) and nirA expression is mediated by the two-component regulator NasS-NasT, an observation that is consistent with the role of this system in other α-proteobacteria [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…The second core cytoplasmic enzyme component of the NO 3 − assimilation pathway is NirA, which is required for growth on either NO 3 − or NO 2 − as sole N-source. Consistent with our findings, it has recently been demonstrated that NirA (encoded by bll4571) is required for utilization of NO 3 − or NO 2 − as sole N-source in B. japonicum [ 46 ]. NO 3 − -dependent induction of nasC (as part of the narK operon) and nirA expression is mediated by the two-component regulator NasS-NasT, an observation that is consistent with the role of this system in other α-proteobacteria [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…With respect to nitrite-dependent growth, the ntrC and rpoN¡/s mutants exhibited a strong delay in growth kinetics, but were nevertheless able to reach WT growth rates after 10 days of incubation. This pattern is in contrast to recent studies where a B. diazoefficiens ntrC mutant was unable to grow with nitrite as the only N source (Franck et al 2015). This apparent discrep ancy could be explained by the different growth conditions used by Frank and colleagues from those used in this work.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been previously demonstrated the involvement of NtrC on nirA expression as well as the inability of a B. diazoefficiens ntrC mutant to grow on nitrite as sole N source (Franck et al 2015). Our biochemical results confirm the NtrC control over nirA and demonstrate for the first time the involvement of NtrC as a transcriptional regulator of the nasC gene encoding the assimilatory nitrate reductase as well as in the ability of B. diazoefficiens to grow with nitrate as the sole nitrogen source.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Though this system has been widely used in a variety of bacterial species, it is prone to yield significant numbers of false-positive, sucrose-resistant clones in some hosts (2)(3)(4)(5)(6). This prompted the development of alternative systems, which, however, may have other limitations, such as species specificity or dependence on additional functions which must be provided in trans (e.g., I-SceI-or cre-and loxP-based systems) (7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%